Neural crest origin of retinal and choroidal pericytes - Trost, Andrea; Schroedl, Falk; Lange, Simona; Rivera, Francisco J.; Tempfer, Herbert; Korntner, Stefanie; Stolt, Claus; Wegner, Michael; Bogner, Barbara; Kaser-Eichberger, Alexandra; Krefft, Karolina; Runge, Christian; et al. (Investigative Ophthalmology & Visual Science, 2013)
The origin of pericytes (PCs) has been controversially discussed and at least three different sources of PCs are proposed: a neural crest, mesodermal, or bone marrow origin. In the present study we investigated a potential neural crest origin of ocular PCs in a transgenic Rosa26-YFP-Sox10-Cre neural crest-specific reporter mouse model at different developmental stages.The Rosa26-YFP-Sox10-Cre mouse model expresses the yellow fluorescent protein (YFP) reporter in cells with an active Sox10 promoter and was here used for cell fate studies of Sox10-positive neural crest derived progeny cells. Detection of the YFP signal in combination with double and triple immunohistochemistry of chondroitin sulfate proteoglycan (NG2), platelet derived growth factor receptor ? (PDGFR?), ? smooth muscle actin (?SMA), oligodendrocyte transcription factor 2 (Olig2), and lectin was performed and analyzed by confocal microscopy.Sox10-YFP-positive cells and profiles were detected in the inner nuclear layer, the ganglionic cell layer, and the axons of the nerve fiber layer in postnatal retinas. An additional population has been identified in the retina, optic nerve, and choroid that displays strong perivascular localization. These cells were colocalized with the PC-specific markers NG2 and PDGFR? in embryonic (E14.5) as well as postnatal (P4, P12, 6-week-old) vasculature. Beside PCs, vascular smooth muscle cells (vSMCs) were also labeled by the Sox10-YFP reporter protein in all ocular tissues investigated.Since YFP-positive PCs and vSMCs are colocalized with NG2 and PDGFR?, we propose that capillary PCs and vSMCs in the retina and the optic nerve, both parts of the central nervous system, as well as in the choroid, a tissue of mesodermal origin, derive from the neural crest.
EVALuna2:4935